Lebanon : Use of Fund Resources; Request for Emergency Post-Conflict Assistance; Staff Report; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This report reviews the Emergency Post-Conflict Assistance (EPCA) given to Lebanon after the conflict with Israel in 2006. The five-week conflict with Israel in 2006 and the month-long blockade that followed inflicted a heavy human and economic toll on Lebanon. EPCA would provide an appropriate transition to 2008, when fiscal adjustment is envisaged to commence. The authorities intend to seek IMF support through a Stand-By Arrangement (SBA), following satisfactory implementation of the EPCA program and after the immediate impact of the conflict has been addressed and the current political stalemate resolved.